Overestimation of on-road driving performance is associated with reduced driving safety in older drivers. (July 2023) - Schlueter, Daniel A.; Austerschmidt, Kim L.; Schulz, Philipp; Beblo, Thomas; Driessen, Martin; Kreisel, Stefan; Toepper, Max
Highlights: We examined the accuracy of on-road self-assessments in older drivers. 75% of older drivers showed an accurate on-road self-assessment. 25% of older drivers overestimated their on-road driving performance. Overestimators showed an increased prospective accident risk. Overestimators appear to represent a risk group. Abstract: Objectives: Older drivers often show less precise self-ratings with a tendency to overestimate themselves. It is unclear, however, how overestimators differ from underestimators or drivers with adequate self-ratings. Methods: 59 healthy older drivers participated in this on-road study. Besides standardized on-road driving assessment, the study protocol included the collection of neuropsychological and driving-related data as well as different self-ratings. Statistical analyses involved correlations between different subjective and objective ratings as well as statistical comparisons between drivers who overestimated and drivers who adequately rated their on-road driving performance (no drivers underestimated their performance). Results: Despite positive correlations between different self- and expert ratings, our results revealed that 25 % of the participants overestimated their on-road driving skills. Among other things, overestimators showed poorer on-road driving performances, more prospective near and minor at-fault accidents, poorer cognitive performances in specific driving-related domains and reduced annual mileage. Discussion: Our results suggest that older drivers who overestimate their driving skills show poorer performances within a broad range of skills that directly reflect or are closely related to driving safety. Against the background that an adequate self-assessment is required by German traffic regulations, our findings suggest that overestimators represent a risk group among the population of older drivers.